2019
DOI: 10.1002/vms3.189
|View full text |Cite
|
Sign up to set email alerts
|

Labelling and quality of antimicrobial products used in chicken flocks in the Mekong Delta of Vietnam

Abstract: Background The Mekong Delta of Vietnam is a hotspot of antimicrobial use (AMU), but there is no information on the quality of the labelling and strength of antimicrobial products used in poultry production. Methods Based on a large random sample of farms, we identified the 20 most used antimicrobial products in the area, and investigated their antimicrobial active ingredient (AAI) content by UPLC‐MS/MS (91 analytical tests). Results Only 17/59 (28.8%) batches contained all AAIs within 10% of the declared stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Farmers often visit these shops to buy animal feed and other supplies ( 17 ). In addition, the antimicrobial product labels often include indications for prophylactic use at a lower dose ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Farmers often visit these shops to buy animal feed and other supplies ( 17 ). In addition, the antimicrobial product labels often include indications for prophylactic use at a lower dose ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences were identified between provinces regarding the typology of farming practices. We can hypothesise that the higher dosages of antibiotic observed in Long An province can be explained by a lower quality of the drug, as it has been Other animals_Yes 4 × 10 − 2 Give an alternative to sick animals_vitamins electrolytes or probiotics 5.0 × 10 − 2 found in the Mekong delta in south Vietnam (Yen et al, 2019). There is also a greater weather variation in the north which was associated with seasonal variation of outbreaks of highly pathogenic avian influenza while it was not the case in the south (Delabouglise et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that approximately one in eight (12%) of veterinary antimicrobial products purchased in the sampled drug stores did not meet the national quality standard of an actual concentration of AAI within ± 10% deviation of what is stated on the label. Other studies on antimicrobial drug quality in Vietnam found 28.8% of antimicrobials for chickens deviated more than ± 10% from the labelled concentration [ 4 ]. In antimicrobial products used in aquaculture, two studies found 1/25 and 6/21 of the products had an actual concentration within ± 10% of the labelled concentration [ 5 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of 20 samples collected from poultry farms, 6 (30.8%) had AAI concentrations within 10% of the labelled content, 8 (39.6%) contained AAI concentrations higher than the labelled content, and 6 (29.7%) had AAI concentrations less than 90% of the content. In total, only 15% of the tested products in this study contained all antimicrobials within ±10% of the concentration stated on the label [ 4 ]. Another study investigated the quality of antimicrobials used in Vietnamese white leg shrimp production.…”
Section: Introductionmentioning
confidence: 99%